PROFESIONALISME GURU DALAM PERSPEKTIF AL-QUR’AN - Suriadi Adi Samsuri (JP : JURNAL PENDIDIKAN, 2018)
Education as a theory of human thinking about the problems of education and efforts to solve it in a fundamental and systematic. While education as a practice is a human activity educates learners to achieve certain idealized goals. Professionalism is a teaching that teaches that every job should be done by a professional person. A professional person is a person who has a profession. In Islam every work must be done professionally, in the sense of being done right. It's only possible by someone who is an expert. Whatever type of profession is carried, it should be done professionally. The teacher's professionalism in the Quran is actually derived from the opinion of the commentators who emphasize the meaning of the word 'ala'atam al-An'am: 135, Hud: 93 and 121, Al-Zumar: 39) and the word' ala syakilatihi (on the letter of Al-Isra: 84). The two words are the word 'ala eatatikum has the meaning of place, degree, position, ability, strength, position, state of a person, peak ability possessed by someone, or a fixed state of something that happens continuously all the time, . From this it can be understood that the Koran gives the signal that work must be done professionally. Similarly, the profession of teachers should be done professionally.